Emergency Wound Infection Monitoring and Treatment Based on Wearable Electrochemical Detection and Drug Release with Conductive Hydrogel - Shaopeng Wang; Songsong Huang; Qian Chen; Yanjun Li; Liyang Duan; Zhi Yu; Weixia Li; Hui Luo; Shuang Li; Bin Fan; Zetao Chen (Chemosensors)
At emergency sites, bacteria in the environment can cause secondary wound infections. Timely treatment of infected wounds can improve the prognosis. In this study, we designed a closed-loop system for real-time wound infection monitoring and electronically controlled drug release, enabling rapid and stable deployment at disaster sites. Multilayer screen-printed electrodes were developed to detect uric acid (UA), pH, and temperature biomarkers. The electrode’s outermost layer was shielded by a zwitterionic conductive hydrogel (Gel) to prevent environmental interference and achieve systematic antibacterial protection through in situ reduction of silver nanoparticles (AgNPs) on its surface. For rapid and efficient drug delivery, amikacin (Ami) loaded cationic liposomes (Lipo) embedded in the zwitterionic conductive hydrogel (Gel-Lipo@Ami) were integrated as the core therapeutic carrier. This closed-loop system provides timely infection detection and enables in situ treatment during emergency rescues.